Pre- and Post-harvest Melatonin Application Boosted Phenolic Compounds Accumulation and Altered Respiratory Characters in Sweet Cherry Fruit - Michailidis, Michail; Tanou, Georgia; Sarrou, Eirini; Karagiannis, Evangelos; Ganopoulos, Ioannis; Martens, Stefan; Molassiotis, Athanassios (Frontiers in Nutrition, 2021)
The aim of the present study was to investigate the impact of exogenous melatonin (0.5 mM) application through preharvest foliar spray and postharvest immersion, alone or in combination, on ripening parameters of sweet cherry (cv. Ferrovia) fruit and their relationship with bioactive compounds and gene expression at harvest as well after cold storage (0 °C) for 12 days and subsequent room temperature (20 °C) exposure for 8 hours. Although several ripening traits were not influenced by melatonin, the combining pre- and post-harvest treatments delayed fruit softening at post-cold period. Preharvest spray with melatonin depressed fruit respiration at time of harvest while all applied treatments induced respiratory activity following cold, indicating that this anti-ripening action of melatonin is reversed by cold. Several genes related to the tricarboxylic acid cycle, such as PaFUM, PaOGDH, PaIDH and PaPDHA1 were upregulated in fruit exposed to melatonin, particularly following combined pre- and post-harvest application. The accumulation of phenolic compounds, such as neochlorogenic acid, chlorogenic acid, epicatechin, procyanidin B1, procyanidin B2+B4, cyanidin-3-O-galactoside and cyanidin-3-O-rutinoside along with the expression of several genes involved in phenols biosynthesis, such as PaSK, PaPAL, Pa4CL, PaC4H and PaFNR were at higher levels in melatonin-treated cherries at harvest and after cold exposure, the highest effects being observed in fruits subjected to both pre- and post-harvest treatments. This study provides a comprehensive understanding of melatonin-responsive ripening framework at different melatonin application conditions and sweet cherry stages, thereby helps to understand the action of this molecule in fruit physiology.